The Lahore Blast: Revisiting the Role of Religion in Pakistan - Mahmood, Sara (2016)
The bomb blast in Lahore on Easter highlights the focus of terrorist groups on attacking religious minorities, and reflects the radicalisation of the broader community. It is time for the state to focus on more fundamental approaches to nation-building.